The Influence of Corporate Governance, Capital Structure, Company Growth on Dividend Policy and Firm Value in Consumer Goods Industry - Karimah, Raudhatul; Rahayu, Sri Mangesti; Rut Damayanti, Cacik (FIA UB, 2024)
This research aims to determine the influence of corporate Governance, capitalstructure, and company growth on dividend policy and company value. The data issecondary data from the financial reports of consumer goods sector companies listed onthe Indonesia Stock Exchange in 2015-2020. The sample for this research consisted of14 companies. This explanatory research uses a quantitative approach and implementsthe Partial Least Square (PLS) approach. This research finds that corporateGovernance, capital structure, and company growth have insignificant effect ondividend policy, while they have a significant impact on company value. Dividend policyhas a negative effect on company value.